Analisis Postur Kerja menggunakan Metode Rapid Upper Limb Assesment (RULA) dan Ovako Work Posture Analysis System (OWAS) pada Awing dan Son - Adistana, Elen; Tranggono, Tranggono (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Awing and Son is a company that produces songkok. Based on observations that have been made, the songkok sewing process is the production part that has the highest level of complaints among other production parts. This research was conducted to identify workers' musculoskeletal disorders and provide recommendations for improvement. This research revealed that by distributing the NBM questionnaire, there were several complaints experienced by workers in the songkok sewing process. Then an analysis was carried out using the RULA and OWAS methods, this method is a method for disseminating and disseminating worker attitudes that can cause musculoskeletal disorders. The research results showed that the RULA method obtained a score of 5 with a risk level of 3, which means that corrective action needs to be taken immediately, while the OWAS score was 3 with a risk level of 2, which means that corrective action can be taken at a later date. Based on these results, proposed improvements can be made by upgrading the adjustable chairs in carrying out work.